2013
DOI: 10.5539/ijms.v5n2p93
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Internet Advertising through Memorization and Click on a Banner

Abstract: The development of the Internet tool was accompanied by a business turnaround which has deep effects on the rules of marketing and particularly the company-customers relationships. The graphical interface that the Web can create between the company and its customers promotes its use as a medium of marketing communication.The advantages of e-communication are endless for companies, including timeliness, cost and interactivity. However, users are daily confronted with large masses of information which may affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…How strong the influence of rational aspects of a product compared to the emotional aspect in the context of the formation of value co-creation, especially in the mobile advertising industry to the telecommunications market, became one of the research gaps in this study. Some previous research also confirms that there is no type of level in the value co-creation itself, especially the study of value co-creation in mobile advertising marketing in the telecommunications industry (Nihel, 2013). This is another research gap and one of the underlying things that this research is doing.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…How strong the influence of rational aspects of a product compared to the emotional aspect in the context of the formation of value co-creation, especially in the mobile advertising industry to the telecommunications market, became one of the research gaps in this study. Some previous research also confirms that there is no type of level in the value co-creation itself, especially the study of value co-creation in mobile advertising marketing in the telecommunications industry (Nihel, 2013). This is another research gap and one of the underlying things that this research is doing.…”
Section: Introductionsupporting
confidence: 54%
“…Based on the model of attribute research and the benefits of acceptance attitude towards online ads (Korgaonkar and Wolin, 2007), click through rate (CTR) measurement model (Nihel, 2013), the cocreation of value exploring engagement behaviors in user generated content websites (Gangi, 2010), and consumer engagement model (Vivek, 2009) the frame of thought in this study is based on several theories as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Advertising is a standard promotional tactic that is desi gned to reach a target audience and to either affect beha vior or to introduce, persuade, and/or remind consumers of an offer (Nihel 2013). Advertising messages could be delivered through various mediums (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For instinct, John & Sathiyaseelan (2014) showed that the top position of ads was most effective, and the right position was least effective in terms of explicit memory, but no significant difference was found as regards implicit memory. Moreover, it was revealed that the users are more likely to click on the banner ad at the top of the screen, the largest banner, animated banners, banners with bright colors (Nihel, 2013). It is widely thought that creative characteristics of online ads also can influence click-through rates (Rosenkrans, 2009).…”
Section: Why Does Web Advertising Design Matter?mentioning
confidence: 99%
“…In Rosenkrans' (2009) empirical investigation, the user reacted more actively to online banner ad designs with creative characteristics. Nevertheless, the main empirical results shown by Nihel (2013) are that memory is mainly affected by the location in the screen, size and animation in banner advertising.…”
Section: Why Does Web Advertising Design Matter?mentioning
confidence: 99%